2015
DOI: 10.7727/wimj.2015.345
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Neutrophil to Lymphocyte Ratio and Monocyte to Lymphocyte Ratio in Gouty Arthritis Attacks

Abstract: Objective: To evaluate neutrophil to lymphocyte ratio (NLR) and monocyte to lymphocyte ratio (MLR) in patients with gouty arthritis. Methods: Forty-five patients with gout and 45 healthy age and gender matched individuals, were included in this study. Clinical and laboratory data of patients during acute gouty arthritis (AGA) attack period, as well as in remission and control group data were reviewed and recorded from medical files. Patients were divided into two groups as having the arthritis attack and in re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Şahin et al reported higher neutrophil to lymphocyte ratios in people with gout compared with both people with gout in remission and healthy controls,55 which is unsurprising given the importance of neutrophils in the resolution of an acute gout attack. Neutrophils have relatively low numbers of mitochondria compared with other white blood cell types,56 57 so elevated neutrophil numbers in blood may result in less mtDNA recovered from the same volume of blood from a study participant.…”
Section: Discussionmentioning
confidence: 99%
“…Şahin et al reported higher neutrophil to lymphocyte ratios in people with gout compared with both people with gout in remission and healthy controls,55 which is unsurprising given the importance of neutrophils in the resolution of an acute gout attack. Neutrophils have relatively low numbers of mitochondria compared with other white blood cell types,56 57 so elevated neutrophil numbers in blood may result in less mtDNA recovered from the same volume of blood from a study participant.…”
Section: Discussionmentioning
confidence: 99%
“…The results of AŞahin were also consistent with this study. 34 Another monocentric and retrospective study 35 also supports this viewpoint, but there are differences. Compared with healthy controls, gout patients showed a significant increase in NLR and PLR (P < 0.001), but a significant decrease in MPV (P < 0.001).…”
Section: Nlr Is Related To Ga Activitymentioning
confidence: 93%
“…However, inflammation remains the most crucial pathological mechanism underlying GA. 6 Following physical examination and history collection, an objective test index is still required to evaluate the inflammatory activity of GA. The aforementioned multiple observational studies have consistently demonstrated the reliable ability of NLR to evaluate inflammatory activity in GA. 21,[33][34][35] Similarly, comorbidities are major contributors to mortality in patients with GA, and NLR has a better significance in predicting GA comorbidities, especially cardiovascular and cerebrovascular diseases and endocrine diseases. 37,40 We need to conduct more large-sample randomized control trials or cohort studies to clarify the clinical value of NLR.…”
Section: Summary and Prospectmentioning
confidence: 99%
“…Monocyte activation and its differentiation to lipid-loaded macrophages have important role in the formation of atherosclerotic lesions. 5 8 High-density lipoprotein cholesterol (HDL-C) has a protective role in cardiovascular diseases due to its anti-inflammatory, antioxidant, and antithrombotic properties. 9 Besides, a relationship between high number of monocytes and low HDL-C levels has been reported in inflammatory disorders.…”
Section: Introductionmentioning
confidence: 99%